A CASE STUDY OF STUDENT PERFORMANCE IN ELECTRIC CIRCUIT 2 SUBJECT - Zaiton , A.M.; Kamarul, A.M.; Mohd Soufhwee , A. R.; Haeryip , Sihombing; Mohd Yuhazri, Y. (2011)
Institution of Higher Learning plays an important role to produce high quality graduates. The most important factor that determines graduates quality shown in their CGPA. In order to maintain high CGPA, students should perform well especially in their examination where it contributes the most in the assessment. Students should mastered basic subject in order to maintain their grades. This survey is to study the reasons for poor performance of the students in Electric Circuit 2 subject. Findings have shown that student’s performance was not only influence by the lecturer but also interrelated to student’s ability and how they see the learning process it either they are a surface or deep learner.